Wear Behavior of Self-mated Ti-Si-C Composites and Ti-Si-N Composites Slid Without Lubricant - Yuko Hibi (Japanese Society of Tribologists, 2008)
To develop lightweight wear-resistant titanium matrix composites, the wear behaviors of three kinds of composites produced from SiC and titanium (Ti-Si-C composite) and three kinds of composites produced from Si3N4, TiN and titanium (Ti-Si-N composite) were evaluated. The composites were slid against themselves without lubricant. The wear of these composites was smaller than that of titanium metal and was influenced by the kind of ceramics in the starting material rather than the amount of the ceramics. The wear resistance of the Ti-Si-N composite was higher than that of the Ti-Si-C composite. Tribo-oxidation took place on the surfaces of the composites during sliding, and the produced oxide abraded and hollowed the Ti-Si-C composite. On the sliding surface of Ti-Si-N composite, however, plastic flow of the oxide was observed.